Muscarinic and Nicotinic Contribution to Contrast Sensitivity of Macaque Area V1 Neurons - Herrero, Jose L.; Gieselmann, Marc A.; Thiele, Alexander (Frontiers in Neural Circuits, 2017)
Acetylcholine is a neuromodulator that shapes information processing in different cortical and subcortical areas. Cell type and location specific cholinergic receptor distributions suggest that acetylcholine in macaque striate cortex should boost feed-forward driven activity, while also reducing population excitability by increasing inhibitory tone. Studies using cholinergic agonists in anaesthetized primate V1 have yielded conflicting evidence for such a proposal. Here we investigated how muscarinic or nicotinic receptor blockade affect neuronal excitability and contrast response functions in awake macaque area V1. Muscarinic or nicotinic receptor blockade caused reduced activity for all contrasts tested, without affecting the contrast where neurons reach their half maximal response (c50). The activity reduction upon muscarinic and nicotinic blockade resulted in reduced neuronal contrast sensitivity, as assessed through neurometric functions. In the majority of cells receptor blockade was best described by a response gain model (a multiplicative scaling of responses), indicating that ACh is involved in signal enhancement, not saliency filtering in macaque V1.